Simulation Analysis of Segment Joint Deformation and Waterproof Performance under High-speed Train Vibration in Large-diameter Shield Tunnel - DU Jiajun; WU Yue; ZHENG Changqing; QI Chun; HUO Yongpeng; YAN Qixiang (Chengshi guidao jiaotong yanjiu, 2024)
Objective To prevent water leakage issues in large-diameter shield tunnel, ensure high-speed train operational safety and normal tunnel functionality, it is necessary to carry out analysis and research on tunnel segment joint deformation and waterproof performance under high-speed train vibration. Method Relying on the Zhanjiang Bay Subsea Tunnel project, a soil-tunnel three-dimensional model and a sealing gasket-groove two-dimensional refined model are established using finite element software. First, the dynamics response and deformation characteristics of segment joints under high-speed train vibration in large-diameter shield tunnel are studied, with longitudinal joints as example. Then, the waterproof performance of a sealing gasket is analyzed based on the most adverse joint deformation working condition. Result & Conclusion The research results indicate that under the vibration of a single high-speed train, the displacement response process of segment joints can be divided into three stages: deformation increase, deformation being danger, and deformation decline. During the second stage, significant joint opening and misalignment occur at the upper part and both ends of the segment ring, while adjacent joints experience reduced opening and misalignment due to compression from both adjacent side segments. There is almost no deformation at the joints below the track bed, as the tunnel track bed significantly mitigates the impact of train vibration on segment linings. The contact stress between sealing gaskets follows a U-shaped distribution, decreasing from the central contact area towards both edges between the sealing gasket and the segment groove. Leakage is more likely to occur at the contact surfaces between the sealing gaskets than along the contact path between the sealing gasket and the segment groove. Under the most adverse working condition of this project, a provided triangular perforated sealing gasket is found to meet the tunnel waterproof requirements.